Pengaruh Inventory Intensity , Kepemilikan Institusional dan Capital Intensity terhadap Agresivitas Pajak dengan Komisaris Independen Sebagai Variabel Moderasi - Wahyu Adi Wibowo; Rima Afita Sari; Parasdya Pandhu Andanawarih (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This research aims to analyze the influence of inventory intensity, institutional ownership and capital intensity on tax aggressiveness with independent commissioners as a moderating variable in basic industrial and chemical companies listed on the Indonesia Stock Exchange in 2019-2023. The research sample consisted of 24 companies with a total of 120 sample data. This research uses secondary data in the form of company financial reports. The sampling technique uses purposive sampling technique with certain criteria. The data analysis method uses panel data regression using Eviews 12th. The research results show that inventory intensity and institutional ownership have no influence on tax aggressiveness. Meanwhile, capital intensity has a positive effect on tax aggressiveness. Apart from that, independent commissioners are unable to moderate the influence of inventory intensity and institutional ownership on tax aggressiveness. However, independent commissioners are able to weaken the influence of capital intensity on tax aggressiveness.